2021
DOI: 10.1002/joc.7255
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal variability in the stratiform/convective rainfall contribution to the summer monsoon rainfall in India

Abstract: Spatio‐temporal variability of contributions of stratiform and convective rainfall to Indian monsoon (June–September) rainfall have been investigated using hourly rainfall data of well distributed 126 stations in India for the period 1969–2015. The criteria used for identifying stratiform rainfall are hourly rainfall ≤5 mm and spatial homogeneity. The study showed that Indian monsoon rainfall exhibits two distinctive features, viz. stratiform component dominating over peninsular (southern) India and convective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The heating associated with rainfall produces convective and stratiform bores from the centre of the heating. The large contribution of stratiform rainfall in distant lee side (DLS) of WG found by Deshpande and Kulkarni (2021) may have contributions from the convection over ILS of WG due to HJ. More modelling studies are required to associate the stratiform rainfall over DLS region and convection over the immediate lee side (ILS) of WG due to HJ.…”
Section: Importance Of the Studymentioning
confidence: 96%
See 2 more Smart Citations
“…The heating associated with rainfall produces convective and stratiform bores from the centre of the heating. The large contribution of stratiform rainfall in distant lee side (DLS) of WG found by Deshpande and Kulkarni (2021) may have contributions from the convection over ILS of WG due to HJ. More modelling studies are required to associate the stratiform rainfall over DLS region and convection over the immediate lee side (ILS) of WG due to HJ.…”
Section: Importance Of the Studymentioning
confidence: 96%
“…Tropical rainfall is classified mainly into (a) convective and (b) stratiform. Microphysically, convective rainfall is characterized by strong cloud updrafts, high rain rates, and small area coverages, while stratiform rainfall are characterized by small cloud vertical velocities, low rainfall rates and widespread area coverages (Deshpande and Kulkarni, 2021; Morwal et al, 2016; 2017; Rickenbach and Rutledge, 1998). The cloud top heights are not very high.…”
Section: Rainfall and Synoptic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the classified the 6-hourly precipitation dataset, Rulfov a and Kyselý (2013) found the convective precipitation and shows stronger positive trends compared with the stratiform precipitation over the Czech Republic in recent decades. Deshpande and Kulkarni (2021) have reported that both convective and stratiform precipitation exhibit decreasing trend in the central India and increasing trend significantly in the western India.…”
Section: Introductionmentioning
confidence: 99%